Variable granularity service function chain mapping algorithm based on microservice architecture - Xiaochun WU; Chen HONG; Yue ZHANG; Junnan ZHANG; Jingjing ZHOU (Dianxin kexue)
For the problem that the end-to-end delay of the service function chain (SFC) cannot meet the demand of delay-sensitive applications in 5G environment, a variable granularity service function chain mapping (VG-SFCM) algorithm based on microservice architecture was proposed by splitting the traditional virtualized network function (VNF) into mapping units of varying granularity.Firstly, the traditional coarse-grained VNF was decoupled into fine-grained microservice units, and then the instantiation of microservice units was reduced through the consolidation of redundant microservice units within SFC and the reuse of microservice units between SFC, thus reducing the processing time of SFC.The simulation results show that the algorithm reduces the end-to-end delay of SFC by 14.81% compared to the traditional mapping algorithm while reducing the average deployment network cost.